The story of Andrew Jackson - Meadowcroft, Enid La Monte 1898-; Hendrickson, David 1896-. (New York Grosset & Dunlap, 1953)
A biography of the President who wasted his inheritance on horse racing and cock fights, fatally wounded a lawyer in a pistol duel, and married a divorcaee in 1791.
Keywords: Jackson, Andrew -- 1767-1845.